The Impact of Safety Through Seat Belt Enforcement Laws - Cabral, Tony Alexander (My University, 2026)
The United States depends significantly on vehicles as a major aspect of transportation. Passenger vehicle occupants were involved in nearly 24,000 unrestrained fatal crashes, which accounted for almost half of those who died. While many citizens use their seat belts, some refuse to buckle up. Research indicates that states that switch their seat belt law from secondary to primary see seat belt usage increase by 10%. One research gap is the motivation of at-risk populations regarding restraint use. The primary purpose of this research is to analyze seat belt use, social vulnerability, and crash outcomes. One unique aspect of this study is that it integrates the Social Vulnerability Index (SVI) data from the CDC by combining SVI and county-level crash data using predictor variables from traffic crashes. The research uses the following analyses: descriptive comparisons, inferential statistics (χ², t tests, logistic regression), overlaying SVI data, and economic calculations. Deterrence theory provides how the certainty, swiftness, and severity of enforcement impact seat belt use compliance. The use of social learning theory helps explain why people choose to wear or not wear seat belts. Understanding the differences in these laws and their impacts across demographics explains how they affect whether someone buckles up.
Keywords: Public administration; Dissertations, Academic; Automobiles--Seat belts--Law and legislation